Cornual pregnancy-high index of suspicion - Chawla, Rachita (International Journal of Research in Medical Sciences, 2018)
Cornual ectopic pregnancy is a rare variant of ectopic pregnancy which requires high index of clinical suspicion and radiological support to manage. The incidence of interstitial pregnancy is rising. Traditional treatment with laparotomy, is associated with high morbidity and detrimental effects on future fertility. A diverse array of alternate treatments has been introduced over the last 3 decades, with the goal of achieving a conservative or inimally invasive management. Here we present such a case.